Characteristics of Anterior Segment Dysgnesis in Pediatric and Strabismus Ophthalmology Unit at Cicendo Eye Hospital 2012-2014 - Ramadanti, Sarah Nurul; Irfani, Irawati; Khairani, Astrid Feinisa (Althea Medical Journal, 2016)
Background: Developmental anomalies in congenital anomalies cause malformation, such as Anterior Segment Dysgenesis (ASD). Disorder in maturation of anterior segment of the eye occurs in ASD, associated with increased risk of glaucoma. This relation is not supported with enough data about characteristics pediatric patients with ASD in Indonesia. The aim of the study was to describe characteristics ASD in pediatric patient Cicendo Eye Hospital based on patientsâ identity, clinical profile and obstetrics profile.Methods: This study used a descriptive method and conducted retrospectively. Data were collected from medical records of patient with ASD in Pediatric Ophthalmology and Strabismus Unit at Cicendo Eye Hospital, from January 2012 to December 2014. This study was conducted from July to November 2015. Total sampling based on inclusion criteria were used in this study. Statistic software was used to analyze data. Results: This study used a descriptive method and conducted retrospectively. Data were collected from medical records of patient with ASD in Pediatric Ophthalmology and Strabismus Unit at Cicendo Eye Hospital, from January 2012 to December 2014. This study was conducted from July to November 2015. Total sampling based on inclusion criteria were used in this study. Statistic software was used to analyze data. Conclusions: Characteristics pediatric patients with ASD at Cicendo Eye Hospital based on patients identity are mostly patients diagnosed in infant age group, from outside Bandung, and mostly boys. Based on clinical profile most diagnosis is congenital glaucoma, bilateral dominantly, and without complication. Based on obstetric profile most patients with ASD were born at term without difficulties. [AMJ.2016;3(4):616â70]Â DOI:Â 10.15850/amj.v3n4.948